Octupole excitations in Cs-141,Cs-144 and the pronounced decrease of dipole moments with neutron number in odd-Z neutron-rich Cs-141,Cs-143,Cs-144 - Luo, Y; Rasmussen, J; Hamilton, J; Ramayya, A; Liu, S; Jones, E; Gore, P; Goodin, C; Stone, N; Zhu, S; Hwang, J; Li, K; et al. (2010)
The level scheme of odd-Z neutron-rich 141Cs (Z=55, N=86) was extended and expanded and that of 144Cs (N=89) was identified for the first time by means of γ-γ-γ coincidence measurements of prompt γ rays in the spontaneous fission of 252Cf with Gammasphere. Spin/parity was assigned to the levels based on angular correlations and level systematics in 141,143Cs. Parity doublets characteristic of both simplex quantum number s=+i and s=-i were proposed in 141Cs. The tests by using rotational frequency ratio ω-(I)/ω+(I) imply octupole vibrations in 141Cs and 143Cs. B(E1)/B(E2) values and electric dipole moments D0 were calculated for 141Cs, and re-determined for 143Cs. It was found that B(E1)/B(E2) values of 141Cs are simplex-dependent and the average value is one order of magnitude larger than that of 143Cs, and the deduced dipole moment D0 of 141Cs is considerably larger than that of 143Cs, and comparable to the N=86 isotone 142Ba. For 144Cs the yrast sequence looks like a well-deformed rotational band, but no octupole band structure was identified in this nucleus. The overall variations of D0 in 141,143,144Cs exhibit a pronounced drop of dipole moment with increasing neutron number in this odd-Z isotopic chain, which may be analogous in nature to the quenching of D0 observed in even-even 146Ba (Z=56, N=90) and 224Ra (Z=88, N=136), and to the drop of D0 in the odd-Z neutron-rich 147La (Z=57, N=90) reported by our collaboration. © 2010.